DO CHILD AND ELDER CARE INFLUENCE WORKTIME OF POLISH EMPLOYEES? - Witkowska, Dorota (Acta Scientiarum Polonorum. Oeconomia, 2019)
Economic activity is an important issue, and it depends on many determinants. The aim of our research is the identification of the most important factors which affect the female and male employees’ worktime in Poland. The research is provided on the basis of individual data, originating from Polish Labour Force Survey. In our study, we estimate econometric models, which are built for: the whole sample and separately for women and men. The models describe number of working hours provided by employees (in a month prior to the survey), which is explained by the characteristics of the employee and workplace. In the study we found out that there are different effects of distinguished factors to the male and female employees’ activity. These differences are especially visible for the variables related to respondents’ family situation, education level and occupation.